Digital Apologetics, Social Media and the Mission of the Catholic Church in Nigeria: An Appraisal - Adekunle, Abiona Lawrence (AKSU Journal of Arts, 2024)
The fathers of the Second Vatican Council (1962-1965) acknowledge the importance of using the means of social communication to proclaim the Gospel. Some people have refuted and continue to denigrate the Christian and or the Catholic faith. Therefore, apologetics is always relevant in evangelisation. This study coined digital apologetics to mean using the social media for apologetics. It aimed at appraising the extent to which the Catholic Church in Nigeria has deployed the social media for apologetics given the contemporary objection to the Catholic faith through the social media. The study adopted the qualitative research design using the narrative approach. It gathered data through formal interviews and informal group interviews, online participant observation and the use of written sources. Research questions were sent to 40 Catholic respondents including laity, religious and priests through WhatsApp, but 34 responded. Findings revealed that the social media was used to attack Christianity and or the Catholic faith, and most Nigerian Catholics were aware. Most Nigerian Catholics did not use their social media handles for apologetics. Among most Nigerian clergy on social media, Fada Oluoma, Fr Kelvin Ugwu, MSP, the Claretian Sisters, and Bishop Godfrey I. Onah have been most visible at engaging in digital apologetics. The study challenges Nigerian Catholics to use their social media handles for apologetics rather than solely reporting social or religious events. It is recommended that Nigerian Catholics, and most especially the Catholic Secretariat of Nigeria (CS
free
Keywords: Catholic Church; Christianity; Digital Apologetics; Evangelisation; Social Media